Functional connectivity density of different suicidal behaviors in adolescents with major depressive disorders - Zhong, Hui; Zhang, Jianzhao; Mo, Daming; Zheng, Hongyu; Li, Mengting; Liu, Wenyuan; Shen, Xiaoshuang; Cao, Xiaomei; Jia, Yanbin (Frontiers in Psychiatry, 2024)
BackgroundSuicidal behavior including suicidal ideation (SI) and suicide attempts (SA) is a common clinical feature of adolescent patients with major depressive disorders (MDD). We hypothesized that differences in functional connectivity density (FCD) exist between adolescent patients with SA and SI, and aimed to investigate the different suicidal behaviors in adolescents patients with MDD17.Methods37 MDD adolescents with SA, 34 MDD adolescents with SI, 20 MDD adolescents without SA and SI (non-suicidal group), and 20 adolescents healthy controls (HC) were enrolled in this study. All participants were scanned using functional magnetic resonance imaging (fMRI) to evaluated the FCD. Between-group differences of all variables were analyzed. The relationships between FCD values and clinical scale scores were also analyzed.ResultsThe FCD of the left inferior occipital gyrus in the SI group was higher than those in the other groups. The FCD in the SA group was higher than that in the control group. The FCD of the right dorsolateral superior frontal gyrus in the SI group was lower than that in the other three groups. The FCD values of the left precentral gyrus in the SI group were higher than those in the other three groups. The left inferior occipital gyrus FCD positively correlated with the suicide factor score of Hamilton Depression Scale (HAMD), and the right dorsolateral superior frontal gyrus negatively correlated with the HAMD suicide factor score but not with the HAMD total score.ConclusionChanges in FCD in adolescent patients with depression and SI can reflect changes in functional connections in the brain.